Pre-service primary school mathematics teachers’ beliefs on mathematics assessment - Kimura Patar Tamba; Wiputra Cendana; Adegoke Adegbite (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
Assessment is an important component in learning mathematics. The practice of mathematics assessment is influenced by teachers' beliefs about the assessment. This study aims to explore the beliefs of primary school mathematics teachers regarding mathematics assessment. The research used quantitative research methods using survey methods to 71 prospective elementary school mathematics teachers. Confidence data regarding mathematics assessment was collected using closed and open questionnaires based on a framework of productive beliefs and unproductive beliefs. Data from closed questionnaires were analyzed using descriptive statistics. Meanwhile, open questionnaire data were analyzed using deductive coding method based on productive and unproductive beliefs. The results showed that prospective elementary school mathematics teachers held mixed beliefs in mathematics assessment. On the one hand, it can be said that the beliefs of prospective elementary school mathematics teachers regarding mathematics assessment tend to be contradictory. These results imply the importance of an attempt to intervene in the beliefs of prospective elementary school mathematics teachers regarding mathematics assessment. Thus, assessment practice can lead to productive assessment, which is to encourage meaningful mathematics learning.